Critical mapping methodology as an analytical tool for the understanding of Greek archaeological production - Chourmouziadi, Anastasia; Daravigka, Klea; Stavridopoulos, Ioannis (Open Science Journal, 2021)
The article attempts a critically mapping of the production process of Greek archaeological product, taking into account both the unexplored, so far, complexity of the process, along with the constantly important social value of the product. Our point of departure has been the challenging of current archaeological notion and practices, which we regard as scientifically suffocating and socially inadequate. In this direction, we attempted a visual panoramic synthesis of the archaeological production process through a critical prism constructed from the reflexivity of archaeological ethnography, the political engagement of militant research and the personal gaze of our autoethnographic approach. Drawing on macroscopic observations and partial comments that have derived from the map, we suggest that the archaeological product of Greece has been long detached from the process that produces it; a fact that justifies both the unchangeable features of the product, as well as the internal fragmentation of the process. We regard our interpretation as only a trigger for substantial dialogue concerning Greek archaeological reality and certainly not as an accomplished research outcome.